Disaster risk areas: perception of residents and urban managers on the phenomenon of house collapse in the city of Nampula, Mozambique (Research, Society and Development, 2025)
This study aimed to understand the phenomenon of housing collapse based on the relationship between residents and the built environment, and the actions of urban managers, in the city of Nampula, Mozambique. Methods: A cross-sectional study with a mixed approach was carried out, involving 96 residents and two local urban management technicians. Data were collected using Post-Occupancy Assessment techniques. Results: Residents showed low technical knowledge about resilient houses, and urban management showed low technical skills to meet disaster risk zones. Conclusions: The poor implementation of urban plans, and the low income of residents to build decent housing in places safe from disasters has contributed to the increase in cases of house collapses.